Parameters of the Infrastructure of the Residential Area and Their Relationship with Cardiovascular Risk Factors - T. A. Mulerova; T. F. Gaziev; E. D. Bazdyrev; E. V. Indukaeva; D. P. Tsygankova; O. V. Nakhratova; A. S. Agienko; G. V. Artamonova (Рациональная фармакотерапия в кардиологии)
Aim. This study determined the level of public satisfaction with neighborhood design features in Kemerovo Oblast and their connection to cardiovascular disease risk factors.Subjects and methods. The study population included 1,598 respondents aged between 35 and 70, with 491 living in rural areas and others living in Kemerovo (1,221 women and 477 men). The assessment of neighborhood environment was done according to residents' subjective opinions about infrastructural features (the Neighborhood Environmental Walkability Scale). Depending on how participants responded to the questionnaire, some of these parameters were identified as adverse.Results. The residents of Kemerovo and rural areas of Kemerovo Oblast identified the following neighborhood design features as adverse: the lack of interesting places in neighborhood environment, the remote location of parks and restaurants, the absence of pavement, busy traffic, and a long distance between home and workplace. In the city, arterial hypertension prevalence was high among men, when grocery, fruit and clothing stores were distant, and among women, when banks, public transport stops were distant and the traffic was heavy. Lipid metabolism disorders were more common among women in urban areas, when there were no interesting places around. Obesity prevalence was high among urban female population, when the following adverse factors were present: the remote location of grocery stores, fruit stores, bank, pharmacy and public transport stops and the absence of pavement. Among rural male population, this risk factor was common when there were no pavements. The highest rate of carbohydrate metabolism disorders was found among women living in villages where the traffic is heavy and public transport stops are far away.Conclusion. The impact of infrastructure on the health status of the living population is a new direction of scientific research. Epidemiological studies in different geographic areas and population groups show significant differences in health status, morbidity and mortality from chronic noncommunicable diseases. To reduce the risks of developing diseases of the cardiovascular system, the formation of a socially comfortable health-saving environment is of great importance.